Welcome to âIndonesiaâ! Feminist Readings of âteach yourself Indonesianâ Self-Learning Language Course1 - Jauhola, Marjaana (Jurnal Hubungan Internasional, 2013)
Coinciding with the celebration of 80 years of Sumpah Pemuda 1928, this paper offers a feminist close reading of the âteach yourself Indonesianâ self-learning language material. âTeach yourself Indonesianâ offers for the English speaking world, ways to learn bahasa Indonesian, but it also offers ways to âdiscoverâ Indonesia and Indonesians. The close reading provided in this paper draws from the perspective that concepts, ideas and norms are constituted through reiteration in everyday social practices, such through repetition of the sixteen learning units of the âteach yourself Indonesianâ. This paper aims to illustrate from the readings of the learning units, who are the ânormalizedâ students of Indonesian language, and who, on the other hand, Indonesians and Indonesia with whom the students will interact, with a particular focus on constructs and boundaries of gender norms. Paper also briefly reflects the âforgottenâ events of May 1998, that form an important part of the authors process of learning Indonesia(n).